La inteligencia emocional y el proceso de aprendizaje en niños del nivel inicial 2 de la Escuela de Educación General Básica “San Isidro Labrador” de la ciudad de Ambato, provincia de Tungurahua. - Sánchez Sailema, Jessica Elizabeth (2023)
The present investigation deals with the study of emotional intelligence and the learning process in children of the initial level 2 of the School of Basic General Education "San Isidro Labrador" of the city of Ambato, province of Tungurahua, its purpose is to analyze how the influence of the emotional intelligence in the learning process. For this, the analysis of the two corresponding study variables was carried out, the first variable is emotional intelligence and the second variable is the learning process, collecting duly validated information. Methodologically, it was an investigation with a mixed approach (qualitative - quantitative), quasi-experimental; Due to the depth of the study, it corresponds to an exploratory, descriptive investigation, due to the inference of data, inductive, deductive, analytical, which allowed the design of two instruments for data collection; an interview applied to teachers and an observation sheet made to children, duly validated. Concluding that emotional intelligence in the learning process intervenes assertively allowing the child to assimilate situations in a better way, developing this intelligence is working directly on emotions in coordination with the brain to stimulate feelings focused on productive and objective actions, complements the logical capacity of the child towards understanding to develop emotional ability and assertive learning through the assimilation of feelings of oneself and others.